The Upaya Guru Ngaji Al-Istiqomah Desa Seribandung dalam Mempersiapkan Generasi Muda yang Berkualitas - Murtosiah, Siti; Nana Khofifah (Program Studi Pendidikan Agama Islam IAIQI Al-Qur'an Al-Ittifaqiyah, 2024)
The purpose of this study is to find out the efforts made by Al-Istiqomah teachers in Seribandung village in preparing a quality young generation, and the obstacles faced by teachers, as well as how to overcome the obstacles that occur. This type of research is field research with a qualitative descriptive approach. The data collection is through observation, interviews, and documentation. Using the triangulation method for data validity. As for data analysis, namely data reduction, data presentation, conclusion and verification. The results of the study show that: 1) the efforts made by the teachers of Al-Istiqomah in Seribandung village in preparing a quality young generation are the need for motivation, faith development, intellectual quality development, charity quality development, and social quality development, 2) the obstacles faced by Al-Istiqomah recitation teachers are first, there are internal factors, such as the lack of responsibility of children for activities such as reciting and children's lack of awareness of the importance of reciting or reading the Qur'an, and then external factors, namely parents who are ignorant of their children and do not care about the seriousness of their children's learning. Meanwhile, factors from the child, such as initially wanting to recite because of the incitement of their friends to play, so that they cancel their intention to study. 3) Efforts to overcome these obstacles are by creating a pleasant learning environment, taking an intensive approach to students such as communicating, inviting them to play games, or quizzes and preparing rewards for diligent children.